Photoacoustic image reconstruction: material detection and acoustical heterogeneities. (24th March 2017) - Schoeder, S; Kronbichler, M; Wall, W A
Abstract: The correct consideration of acoustical heterogeneities in the context of photoacoustic image reconstruction is an open topic. In this publication a physically motivated algorithm is proposed that reconstructs the optical absorption and diffusion coefficients using a gradient-based scheme. The simultaneous reconstruction of both material properties allows for a subsequent material identification and an accordant update of the acoustical material properties. The algorithm is general in terms of illumination scenarios, detection geometries and applications. No prior knowledge on material distributions needs to be provided, only expected materials have to be specified. Numerical experiments are performed to gain insight into the complex inverse problem and to validate the proposed method. Results show that acoustical heterogeneities are correctly detected improving the optical images.